Efficacy of Dry Cupping versus Counselling with Mindfulness-based Cognitive Therapy Approach on Fertility Quality of Life and Conception Success in Infertile Women due to Polycystic Ovary Syndrome: A Pilot Randomized Clinical Trial - Fahimeh Baghbani; katayoun Alidousti; Mohammad Mahdi Parvizi; Atefeh Ahmadi; Shaghayegh Moradi Alamdarloo; Amir Mohammad Jaladat; Fatemeh Atarzadeh (Shiraz University of Medical Sciences, 2024)
Background: Physical and psychological interventions could affect the quality of life (QoL) of women with infertility. The purpose of this study was to compare the effectiveness of dry cupping and counselling with the mindfulness-based cognitive therapy (MBCT) approach on fertility QoL and conception success in infertile women due to polycystic ovary syndrome (PCOS).Methods: This was a two-arm pilot randomized clinical trial from first January 2021 to the end of November 2022. In this regard, 19 women with infertility who were referred to the health centers affiliated with Shiraz University of Medical Sciences and met the inclusion criteria were enrolled in the study. Participants were randomly divided into two groups (10 in the virtual MBCT group and 9 in the cupping group). All participants completed the fertility quality of life (FertiQol) tool before the intervention and three months after the end of the intervention. In addition, after the end of the intervention, a human chorionic gonadotropin test was performed monthly for three months, too. We used ANOVA/ANCOVA and its related effect sizes, including mean difference (MD) and standard mean difference (SMD: Hedges's g), and chi-square tests to compare the study group outcomes in Stata 14.2. P-values equal to or less than 0.10 were considered significant.Results: The intervention resulted in significant differences in the mean overall scores of FertiQol between the counseling and cupping groups (61.76±14.28 and 50.65±12.53, respectively) [P=0.091, MD=11.11 (90% CI: 0.33 to 21.89), SMD=1.07 (90%: CI 0.279 to 1.84)]. No significant difference was found in conception rates between the groups after the intervention.Conclusion: This pilot study found that MBCT improved the fertility QoL in PCOS-related infertility patients better than cupping therapy.Trial registration: IRCT201706110334452N13